The legal purposes and their impact on protecting the Muslim from deviation - Agha, Housin Mohammed (Journal of Humanities & Social Sciences, 2025)
This is an original study of the impact of legitimate purposes in protecting the Muslim from deviation, aimed at introducing the legitimate purposes, indicating their importance, and mentioning the types of purposes according to the different circumstances, indicating their impact on protecting the Muslim from deviation, with its exaggeration and idleness, pursuing accuracy, following the deductive rooting approach, and descriptive and analytical, the result of which is to prove the great impact of the legitimate purposes in protecting the Muslim from deviation, before it occurs by preventing it, and after its occurrence by treating it.